Español - Español, Español; Español, Español; Español, Español; Español, Español (Ars Pharmaceutica (Internet), 1991)
In the study that we present are showed several morphological characteristics of Leptosols, Regosols, Calcisols, Luvisols and Cambisols located at SW of Sierra Nevada, as well the parameters which have incidence on their erosive degradation (hydric erosion and eolic erosibity) and their intensity fluctuations for each case.